Comparison of different approaches to small saphenous vein reflux treatment: a retrospective study in two centers - Kubat, Emre; Ünal, Celal Selçuk; Geldi, Onur; Çetin, Erdem; Keskin, Aydin; Karapınar, Kasım (São Paulo Medical Journal, 2020)
BACKGROUND: Diagnosis and treatment of small saphenous vein (SSV) insufficiency is of utmost importance for relieving chronic venous insufficiency symptoms. OBJECTIVES: To investigate the efficacy and safety of five different treatment approaches among patients with SSV insufficiency. DESIGN AND SETTING: Two-center retrospective clinical study, conducted at cardiovascular surgery clinics in a local training and research hospital and a state hospital. METHODS: A total of 282 extremities of 268 patients with SSV insufficiency alone who were treated for symptomatic varicose veins between January 2012 and January 2017 were included in the study. All extremities included in the study were divided into five groups as follows: high ligation + stripping; radiof-requency ablation (RFA); cyanoacrylate closure (CAC); and endovenous laser ablation (EVLA) at the wave-lengths 980 nm and 1,470 nm. RESULTS: Although the recurrence rate at six months was similar among the treatment groups, we found significant differences in recurrence rates at one year, with lower rates in the CAC, RFA and 1,470 nm EVLA groups, compared with the other treatments (P = 0.005). No sural neuritis was observed in the CAC group. The pigmentation rate was higher in the two EVLA groups (980 nm and 1,470 nm). CONCLUSIONS: Our study results showed that although CAC, RFA and EVLA at 1,470 nm seemed to be effective methods for treating SSV insufficiency alone, CAC and RFA had better aesthetic results than EVLA at 1,470 nm. We consider that endovenous non-thermal techniques for treating SSV insufficiency may be preferable because of relatively low risk of nerve injury.